Biology of Acinetobacter baumannii: Pathogenesis, Antibiotic Resistance Mechanisms, and Prospective Treatment Options - Lee, Chang-Ro; Lee, Jung Hun; Park, Moonhee; Park, Kwang Seung; Bae, Il Kwon; Kim, Young Bae; Cha, Chang-Jun; Jeong, Byeong Chul; Lee, Sang Hee (Frontiers in Cellular and Infection Microbiology, 2017)
Acinetobacter baumannii is undoubtedly one of the most successful pathogens responsible for hospital-acquired nosocomial infections in the modern healthcare system. Due to the prevalence of infections and outbreaks caused by multi-drug resistant A. baumannii, few antibiotics are effective for treating infections caused by this pathogen. To overcome this problem, knowledge of the pathogenesis and antibiotic resistance mechanisms of A. baumannii is important. In this review, we summarize current studies on the virulence factors that contribute to A. baumannii pathogenesis, including porins, capsular polysaccharides, lipopolysaccharides, phospholipases, outer membrane vesicles, metal acquisition systems, and protein secretion systems. Mechanisms of antibiotic resistance of this organism, including acquirement of β-lactamases, up-regulation of multidrug efflux pumps, modification of aminoglycosides, permeability defects, and alteration of target sites, are also discussed. Lastly, novel prospective treatment options for infections caused by multi-drug resistant A. baumannii are summarized.